Effects of HIIT and sprint interval training on adiposity in overweight adults: a meta-analysis - Liu, Haochong; Li, Qian; Yang, Wenpu; Poon, Eric Tsz-Chun; Liu, Haoyang; Bao, Dapeng; Ho, Indy Man Kit (International Journal of Sports Medicine)
A meta-analysis was conducted to compare the effects of high-intensity interval training (HIIT) and sprint interval training (SIT) on body fat reduction in adults with overweight or obesity. Following PRISMA 2020 guidelines, eight databases were searched, yielding 10 relevant studies involving 343 participants. Both HIIT and SIT significantly reduced body fat% (standardized mean difference [SMD]=-0.56, 95% confidence interval [CI] = (-0.89, -0.24), p = 0.001 and SMD=-0.57, 95% CI= (-0.85, -0.29), p= 0.000, respectively), fat mass (-0.62(-1.01, -0.23), p = 0.002 and -0.51 (-0.81, -0.21), p = 0.001, respectively), and body mass (-0.43 (-0.75, -0.11), p = 0.009 and -0.34(-0.58, -0.10), p = 0.006, respectively). No significant differences were found between HIIT and SIT in terms of body composition changes. However, the time spent on SIT was approximately 50% less than that of HIIT. Subgroup analysis suggested that SIT with shorter work durations (less than 10s) was more effective in obesity control. In conclusion, both HIIT and SIT demonstrated similar effectiveness in improving body adiposity. Given its time efficiency and straightforward intensity monitoring, SIT may serve as a viable alternative exercise program for promoting fat reduction in adults with overweight or obesity, provided it is appropriately designed.